Role of Incentive Spirometry On Management of Postoperative Pulmonary Complications in Elderly Urology Patients - Afzalul Haque, Abul Hasanat Muhammad; Abedin, Mohammad Raisul; Zaman, Md Farooque z; Shoma, Farzana Khan; Bhuiyan, Abdullah Tareq; Kollol, Humayun Kabir (Journal of Dhaka Medical College, 2023)
Background: Incentive spirometry (IS) is a device used to improve pulmonary function. It is a device that provides patients with visual feedback when they inhale at a predetermined flow rate/volume, sustain the inflation for a minimum of 3 seconds, and then expire. It is postulated that incentive spirometry (IS) might play a significant role in preventing and treating postoperative pulmonary complications. However, we need more research-based information on this issue. Objective: The aim of the study was to assess the effectiveness of incentive spirometry in improving pulmonary function following urologic surgery in elderly patients. Methods: This comparative study was conducted in the department of Urology, Dhaka medical college hospital (DMCH), Dhaka, Bangladesh, from January 2021 to December 2021. In total, 150 elderly people were included as the study subjects. The total subjects were divided into two groups. In group A, there were 75 patients who received incentive spirometry in addition to deep breathing, coughing and early ambulation. In Group B, there were also 75 patients, denoted as control group patients, who received standard care of treatment including deep breathing, coughing and early ambulation without incentive spirometry. All data were collected, processed, and analyzed by using MS Office and SPSS-18 programs as per need. Results: In this study in incentive spirometry, postoperative VAS, FVC, FEV1, and FEV1/FVC scores were 5.29±1.73, 1.25±0.61, 1.21±0.45 and 88.61±18.44 respectively. On the other hand, in Group B (Non incentive spirometry), postoperative VAS, FVC, FEV1, and FEV1/FVC scores were 5.71±1.57, 1.14±0.56, 1.09±0.22 and 91.57±19.91 respectively. We found a significant correlation in comparing FEV1 (Forced Expiratory Volume) between both groups, with a P value of 0.040. In this study, in Group A (IS), only 8% of elderly patients of urological surgery were found with postoperative pulmonary complications. On the other hand, in patients without using Incentive spirometry, one-fifth (20%) were with postoperative pulmonary complications. Conclusion: As per the findings of this study, both treatment methods are effective. But patients’ compliance may be better in applying Incentive spirometry (IS) in urological surgery in elderly patients. Physicians can minimize the possibilities of postoperative pulmonary complications by using Incentive spirometry. J Dhaka Med Coll. 2022; 31(1) : 51-55